2007
DOI: 10.4103/0970-4388.37014
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between audio and audiovisual distraction techniques in managing anxious pediatric dental patients

Abstract: Pain is not the sole reason for fear of dentistry. Anxiety or the fear of unknown during dental treatment is a major factor and it has been the major concern for dentists for a long time. Therefore, the main aim of this study was to evaluate and compare the two distraction techniques, viz, audio distraction and audiovisual distraction, in management of anxious pediatric dental patients. Sixty children aged between 4-8 years were divided into three groups. Each child had four dental visits--screening visit, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
37
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(48 citation statements)
references
References 0 publications
7
37
1
3
Order By: Relevance
“…A number of studies have tried to assess the patient satisfaction after preanesthetic visit, comparing different methods, e.g., face-to-face interviews, brochures, audio tapes, preoperative video information, with varying results. [ 13 14 ] However, very little consideration has been given to patient education, information gain (IG), and patient anxiety levels.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have tried to assess the patient satisfaction after preanesthetic visit, comparing different methods, e.g., face-to-face interviews, brochures, audio tapes, preoperative video information, with varying results. [ 13 14 ] However, very little consideration has been given to patient education, information gain (IG), and patient anxiety levels.…”
Section: Introductionmentioning
confidence: 99%
“…Recent dental studies[ 6 7 8 9 10 ] have shown that distraction is a common technique used to reduce the pain reaction during short invasive procedures. Distraction techniques such as television watching, use of virtual reality, audiovisual eyeglasses, and listening to music may effectively help to distract the child's attention away from anxiety-provoking stimuli, leading to a relaxing experience for the child.…”
Section: Introductionmentioning
confidence: 99%
“…During the administration of a local anesthetic injection, an anxious patient might perceive more pain of longer duration as compared to less anxious patients. [ 6 ] Some studies[ 11 12 ] documented that computerized delivery system (CDS) for local anesthesia caused low levels of stress and pain reaction. The CDS works with a microprocessor which permits controlled low-pressure delivery of the anesthetic solution.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the model of VR device used, it may block out the real-world by hindering the visual, auditory, or both the stimuli. 7 So, the aim of present study was to assess the pain perception and anxiety of children by using virtual reality distraction. The hypothesis will be null hypothesis, i.e., neither or nor virtual reality distraction is related to anxiety and pain perception.…”
Section: Introductionmentioning
confidence: 99%